وێنەى کاریکــــاتێرىلە چەند شیعرێکى داشۆرینى( شێخ ڕەزاى تاڵەبــــانى ) دا - علي, طاهر محەمەد (Sulaimani Journal for Humanities, 2007)
This research studies the poetic images in Kurdish satiric poems. It is mainly about dual intermixed relations, which mirror themselves in the relation between poetic images and tableaus on one hand, and satiric images in poems and caricature pictures on the other hand. In fact the first relation, to so extent, is found in universal literature and Kurdish literature as well, yet the later relation is totally new in Kurdish literature and no research has been done on it. Therefore the focus of this study is more on the second relation in detail from theoretical and practical perspective with reference to some satirical poems of ‘Shekh Razay Talabani’.